Digital Environment and AI in International Education: The Gaps and Implications - Chang, Shanton; Cheong, Marc; Oliveira, Eduardo Araujo (International Higher Education, 2024)
<h3 id="the-impact-of-increased-digitization-and-use-of-ai-on-international-education-is-not-yet-fully-understood-with-practice-advancing-faster-than-research-and-evaluation-this-article-highlights-how-ai-and-the-digital-environment-influence-international-education-addressing-misconceptions-and-highlighting-key-areas-affected-it-advocates-for-interdisciplinary-collaborations-to-bridge-research-gaps-and-meet-the-sectors-evolving-needs" data-pm-slice="1 1 []">The impact of increased digitization and use of AI on international education is not yet fully understood, with practice advancing faster than research and evaluation. This article highlights how AI and the digital environment influence international education, addressing misconceptions and highlighting key areas affected. It advocates for interdisciplinary collaborations to bridge research gaps and meet the sector’s evolving needs.